The effect of braille 3g modified audio tactile media on dental health status of visually impaired children - Widodo, Yufen; Hamid, Abu (Odonto : Dental Journal, 2023)
Background: The poor condition of the visually impaired’s mouth is in consequence of unsupervised brushing teeth, technical errors in brushing the teeth, motor skill and guidance that are still neglected. To overcome these things, it requires special media namely braille media and an innovative technique known as audio tactile technique. Methods: This study used quasi-experimental method with pre-test and post-test one group design which population and sample were visually impaired children in Special Needs School: Rehabilitation Center for the Blind and Visually Impaired (SLB-A PRPCN) Palembang. The total of the sample was 21 children which divided into three treatment groups (Braille 3G Media, Audio Tactile, and Braille 3G Modified Audio Tactile). The status of Dental and Oral Health of children was assessed by using plaque score assessment in the form of Patient Hygiene Performance Index for one month and two month with Anova-test analysis. Results: The result shows that there is a very striking difference in plaque after one month (0.019) and after two months (0.030). Further analysis with the Post Hoc test shows that the groups that differed significantly in the plaque index after one month and two months are braille with modification and audio tactile with modification. Conclusion: From the evidence, we can see that the braille 3G modified audio tactile media is more effective in reducing the plaque index because it can improve the dental health status of visually impaired children.